PENGARUH MEDIA SOSIAL DAN FOMO FINANSIAL TERHADAP MANAJEMEN KEUANGAN PRIBADI MAHASISWA - Hatimatunnisani, Hani; Sandi Aryanti, Shofi; Pancawati, Kurnia; Eri Sutrisno, Krisna; Hermawan, Wawan (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2024)
This study investigates the influence of social media usage and financial fear of missing out (FOMO) on the personal financial management of 52 students from Politeknik Pajajaran. A quantitative method with multiple linear regression was used to analyze questionnaire data. The results show that social media usage is positively and significantly correlated with financial management, while financial FOMO is negatively and significantly correlated. The regression model explains 32.3% of the variance in financial management that can be explained by social media and financial FOMO. These findings indicate the importance of financial literacy and strategies to mitigate FOMO in improving students' financial management. The implications of this research highlight the need for the integration of financial education into the curriculum and the development of financial counseling programs for students.